2012
DOI: 10.1002/anie.201206918
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Reactivity in a Rhodium(III)‐Catalyzed Oxidative Coupling of N‐Allyl Arenesulfonamides with Alkynes

Abstract: Scheme 2. Intermediacy of a 1,2-dihydropyridine. Scheme 3. Mechanism of the formation of 3-sulfonated pyridines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Recently, several investigations revealed that Rh III complexes undergo chelation-assisted electrophilic metalation of ortho CA C H T U N G T R E N N U N G (sp 2 )ÀH bonds to form arylrhodium complexes, [14] which may be coupled to a variety of reagents such as aldehydes, [15] imines, [16] isocyanates, [17] diazomalonates, [18] azides, [19] alkenes, and alkynes (Scheme 1 b). [20] Therefore, herein, we report the first example of Rh III -catalyzed amidation of aldehydes with azides as an amine source in the presence of air (Scheme 1 c). This catalytic aldehyde C À H amidation proceeds in the absence of external oxidants and additives, under mild and neutral reaction, conditions with high functional group tolerance, and releases N 2 as the single byproduct.…”
mentioning
confidence: 97%
“…Recently, several investigations revealed that Rh III complexes undergo chelation-assisted electrophilic metalation of ortho CA C H T U N G T R E N N U N G (sp 2 )ÀH bonds to form arylrhodium complexes, [14] which may be coupled to a variety of reagents such as aldehydes, [15] imines, [16] isocyanates, [17] diazomalonates, [18] azides, [19] alkenes, and alkynes (Scheme 1 b). [20] Therefore, herein, we report the first example of Rh III -catalyzed amidation of aldehydes with azides as an amine source in the presence of air (Scheme 1 c). This catalytic aldehyde C À H amidation proceeds in the absence of external oxidants and additives, under mild and neutral reaction, conditions with high functional group tolerance, and releases N 2 as the single byproduct.…”
mentioning
confidence: 97%
“… 5 The discovery of new cycloadditions based on the activation of olefinic or aliphatic C–H bonds, which would allow the formation of carbocyclic products other than fused aromatic systems, is of foremost interest. 6 …”
mentioning
confidence: 99%
“…Very recently, Rh III complexes have stood out as efficient catalysts for the CÀH activation of a large array of CÀH bonds. [3] Along with the extensively studied rhodium(III)-catalyzed functionalization of CÀH bonds with alkynes [4] and alkenes, [5] the coupling partners have been extended to other substrates, such as imines, [6] aldehydes, [7] isocyanates, [8] allenes, [9] sulfonyl azides, [10] chloroamines, and N-halosuccinimides, [11] and carbene precursors such as diazomalonates [12] in redox-neutral reactions (Scheme 1). These coupling partners are electrophiles that typically react with Grignard reagents to allow CÀC and CÀN couplings starting from arenes.…”
mentioning
confidence: 99%